Defining National Solutions for Managing Book Collections and Improving Digital Access - Grindley, Neil; Marchionni, Paola (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
In 2013 the National Monographs Strategy (NMS) project in the UK explored the potential for a national approach to the collection, preservation, supply and digitisation of scholarly monographs. The resulting NMS Roadmap recommended seven components, believed to be critical for the provision of a national monograph infrastructure. This paper discusses how Jisc prioritised three of the recommendations and started planning for the development of a National Bibliographic Knowledgebase (NBK) in association with key stakeholders representing UK Higher Education and the British Library. In parallel, Jisc also explored recommendations around a national digitisation strategy and national licensing approaches by establishing a ‘Digital Access’ strand of activities.